Evaluation of Quality and Storage Stability of Commercially Produced Dried Fish of Tengra (Mystus vittatus) with Laboratory Produced Dried Fish Products - Begum, Mohajira; Akter, Tanjina; Ahmed, Abu T. A.; Khaleque, Md. A. (International Journal of Bio-resource and Stress Management, 2011)
To evaluate the performance and quality of the commercially sun dried fish the present study was designed and conducted by carrying out production of experimentally sun dried fish for a comparative study. It was observed that the experimentally sun dried tengra fish in laboratory contained moisture 15.10-16.90%, protein 58.02-63.21%, fat 8.01-10.50%, and ash 8-10.50%. The commercially sun dried tengra collected from the local market contained moisture 21.05-23.50%, protein 52.10-55.31%, fat 9.02-12%, and ash 12.50-14%. The quality deterioration of the dried fish was studied by observing physical changes such as color, texture, odor and visual appearance by acceptability score technique and change in chemical index of total volatile nitrogen (TVN). The TVN value gradually increased as the quality of the fish products decreased. In case of experimentally sun dried tengra fish the highest TVN value was found 330 mg 100-1 g of fish while in the commercially sun dried tengra fish it was 390 mg 100-1g of fish. A direct relationship between moisture and TVN value and an inverse relationship between sensory score and TVN value was observed. The moisture content of the fish product gradually increased as the protein content of the products decreased.